In vivo analysis of torsadogenic potential of an antipsychotic drug paliperidone using the acute atrioventricular block rabbit as a proarrhythmia model - Mihoko Hagiwara; Ryuichi Kambayashi; Megumi Aimoto; Yoshinobu Nagasawa; Akira Takahara (Elsevier, 2016)
We assessed electrophysiological effects of an atypical antipsychotic drug paliperidone in acute atrioventricular block rabbits. Intravenous administration of paliperidone at a clinically relevant dose (0.06 mg/kg) hardly affected the QT interval or monophasic action potential (MAP) duration, and the higher doses (0.6 and 6 mg/kg) prolonged the QT interval and MAP duration. Meanwhile, premature ventricular contractions with R on T phenomenon were observed in 3 out of 6 animals at the middle dose, and torsades de pointes (TdP) episodes were detected in 2 out of 6 animals at the high dose. Intravenous administration of its chemically related compound risperidone at a clinically relevant dose (0.03 mg/kg) hardly affected the electrophysiological parameters, and the higher doses (0.3 and 3 mg/kg) prolonged the QT interval and MAP duration. Meanwhile, the premature ventricular contractions with R on T were observed in 2 out of 6 animals at the middle dose, and TdP episodes were detected in 4 out of 6 animals at the high dose. These results suggest that paliperidone showed torsadogenic potential at supra-therapeutic doses, whose potency can be estimated to be equal or slightly subordinate in comparison with that of risperidone.